1992
DOI: 10.1099/00221287-138-10-2145
|View full text |Cite
|
Sign up to set email alerts
|

Global transcription pattern of  C31 after induction of a Streptomyces coelicolor lysogen at different growth stages

Abstract: Using two complementary strategies for low-resolution Sl mapping, the global pattern of (bC31 transcription was studied after induction of thermoinducible (bC31 lysogens of Streptomyces coelicolor A3(2). A complex pattern of early transcripts was seen, with a peak of abundance at about 10 min post-induction. Nearly all of these transcripts were from DNA located to the right of the c (repressor) gene and to the left of the attP site: a region of about 14 kb. Early transcription was also observed immediately to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…When this blot was stripped and reprobed with a segment of orfg4, the same growth-phase-dependent expression pattern as for orfg2 was seen (data not shown). The RNAs complementary to the orfg4 probe also showed size heterogeneity, but over a different size range than for orfg2, consistent with the idea that a primary transcript is rapidly degraded to yield a variety of RNA molecules encoding GTA proteins, analogous to the transcripts of phage C31 (44,45). When ctrA was disrupted (strain YCKF) there were no detectable orfg2 or orfg4 transcripts, which explains the absence of GTA production in ctrA mutants.…”
Section: Gta Structural Genessupporting
confidence: 51%
See 1 more Smart Citation
“…When this blot was stripped and reprobed with a segment of orfg4, the same growth-phase-dependent expression pattern as for orfg2 was seen (data not shown). The RNAs complementary to the orfg4 probe also showed size heterogeneity, but over a different size range than for orfg2, consistent with the idea that a primary transcript is rapidly degraded to yield a variety of RNA molecules encoding GTA proteins, analogous to the transcripts of phage C31 (44,45). When ctrA was disrupted (strain YCKF) there were no detectable orfg2 or orfg4 transcripts, which explains the absence of GTA production in ctrA mutants.…”
Section: Gta Structural Genessupporting
confidence: 51%
“…1 could contain all the information needed for assembly of the GTA head and tail structures and DNA packaging. In the related phage øC31, transcription of the head and tail genes is driven by a single promoter (44,45), and gene organization of the headtail region is a highly conserved feature amongst doublestranded DNA phages (48). Sequence differences between the GTA genes and phage homologs evidently account for the differences in terms of quantity and quality of DNA that is packaged.…”
Section: Discussionmentioning
confidence: 99%
“…A global study of transcription in 4C31 demonstrated that late lytic transcription on the left-hand arm largely resulted in a single, unstable mRNA, whilst discrete, presumably more stable transcripts were detected over the cos region (Suarez et al, 1992). The locations of the late transcripts were approximate and their directionality was not defined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to plasmid-based vectors, phages have proven to be useful tools for studying the biology of their hosts, as they can affect the metabolism of the hosts (22) and can be used in the transfer of genetic information by both transduction and transfection (9). A temperate phage could provide the basis of a cloning system similar to that of the Streptomyces-specific ⌽C31 derivatives (4,18,27) or the phage R4-derived cosmid (16,19).…”
mentioning
confidence: 99%